Health in Writings of Polish Renaissance - Marek Smoła (University of Applied Sciences in Tarnow, Poland, 2022)
The above short analysis of scientific and medical, medicine and didactic treaties of the age of Renaissance allows us to present numerous motifs linked to health and physical fitness, which were in the realm of interest of Polish authors. Not all their statements were original, many notions  were taken from ancient scholars. Nevertheless, Polish Renaissance writers undertook the challenge of independent deliberations over the matter of health, formulating- also in a naive way- many faulty theories. These achievements are worth acknowledging. The scholars mentioned in the above article were in many cases forerunners and originators of certain proceedings which undoubtedly in their times were innovative and ground-breaking.